EFEKTIVITAS BERBAGAI MEDIA EDUKASI KESEHATAN REPRODUKSI DALAM MENINGKATKAN PEMAHAMAN PENCEGAHAN KEHAMILAN REMAJA: (STUDI LITERATUR) - Hardianti, Minarni; Kusuma, Widya Tresna; Adnani, Qorinah Estiningtyas Sakilah; Susiarno, Hadi (Media Penelitian dan Pengembangan Kesehatan, 2025)
The high rate of teenage pregnancy is a serious public health issue caused by limited reproductive health knowledge. Inadequate education makes adolescents vulnerable to risky behaviors, emphasizing the need for appropriate approaches, such as audio-visual media, to enhance understanding. This study comprehensively reviews research on reproductive health education for teenage pregnancy prevention. This study employs a literature review method. Data was collected from PubMed, Google Scholar, Semantic Scholar, and Science Direct using adolescent reproductive health and teenage pregnancy from September to October 2024. Inclusion criteria included studies in Indonesian or English, empirical studies on reproductive health education interventions, adolescents aged 10–19 years who had never been pregnant, full-text availability, and publications from 2019 to 2024. Of 854 identified articles, 7 met the inclusion criteria and were analyzed using a narrative synthesis approach. Findings indicate that reproductive health education improves adolescents' knowledge and attitudes toward pregnancy prevention. Educational interventions using media such as audio-visual content, comics, and videos are highly effective. Adolescents with previously limited awareness showed significant improvement after receiving reproductive health education. These findings highlight the importance of developing tailored educational strategies, particularly media-based programs, to effectively reduce teenage pregnancy rates